"We are not the people they think we are": First-generation undocumented immigrant belonging and legal consciousness in the wake of deferred action for parents of Americans. (February 2022) - Solórzano, Lizette G
On 20 November 2014, President Barack Obama introduced Deferred Action for Parents of Americans and Lawful Permanent Residents (DAPA) as a temporary relief for undocumented immigrant parents raising citizen children in the United States. DAPA's implementation stalled indefinitely following a court-issued injunction in 2015, subsequent legal contestation, and a Supreme Court decision in 2016 upholding the original injunction. I purport that both DAPA and its failure to implement constitute sites from within which to critically examine the legal consciousness and sense of belonging of undocumented participants. By bridging scholarship on legal consciousness and belonging, this article examines how Latino first-generation undocumented immigrants from Los Angeles, who considered DAPA, understand their unlawful presence and assert belonging in the United States (US). This article draws on participant observation in Los Angeles, California, including four DAPA legal information forums and 24 in-depth interviews following DAPA's court injunction with undocumented parents who intended to apply to DAPA. Data reveal a legal consciousness imbued with normative and value-based notions of substantive citizenship including parenthood, law-abidingness, and contribution. In light of DAPA's failure, participants draw on these narratives to counter-assert their belonging and deservingness of DAPA. Ultimately, this case draws attention to how undocumented, first-generation immigrant legal consciousness is more complex than previously ascertained, and how DAPA shapes immigrants' claims to a lawful presence.